Efektivitas pendampingan implementasi kurikulum 2013 untuk meningkatkan kemampuan guru melaksanakan pembelajaran - Toto Raharjo (Lembaga Pengembangan Pembelajaran Penelitian dan Pengabdian Masyarakat Universitas PGRI Mahadewa Indonesia, 2020)
This research aims to determine the effectiveness of the implementation of the 2013 curriculum implementation assistance activities in improving the ability of teachers to carry out learning. This research uses a mixed methods research design, carried out quantitatively and qualitatively and uses the method (research) evaluation. Data collection techniques through questionnaires, observation and interviews. Observations were made on the results of the accompanying documents in the form of a review of the Learning Implementation Plan (RPP) and the results of classroom observations. Quantitative data analysis uses descriptive statistics, while qualitative data analysis consists of three main activities, they are data reduction, data presentation and drawing conclusions. The results showed that: The first, based on an analysis of research results at the reaction level, learning level and application level stated that the activities of the 2013 curriculum implementation assistance were effective in increasing the ability of teachers to carry out learning. The second, there was an increase of 4.8% of the results of the study of RPP and 12.77% of the observation results of learning after the teacher participated in coaching activities. The third, the weakness of the coaching activities in the implementation of the 2013 curriculum was due to the implementation factors that did not fully follow the technical instructions, the ability of the teacher assistants and the recruitment process, the commitment of couchee, the coaching time was too short, and the facilities which is considered inadequate. The strength of the mentoring activities, among others: is considered good, helps the teacher, is useful and needs to be continued. Besides this activity is felt to be able to increase knowledge, understanding, insight and experience for the teacher. Based on the results of the research it can be concluded that the coaching of the implementation of the 2013 curriculum effective in improving the ability of teachers to carry out learning. Penelitian ini bertujuan untuk mengetahui efektivitas pelaksanaan kegiatan pendampingan implementasi kurikulum 2013 dalam meningkatkan kemampuan guru melaksanakan pembelajaran. Penelitian ini menggunakan disain penelitian mixed methods, dilakukan secara kuantitatif dan kualitatif dan menggunakan metode (penelitian) evaluasi. Teknik pengumpulan data melalui angket, pengamatan dan wawancara. Pengamatan dilakukan terhadap dokumen hasil pendampingan berupa hasil telaah Rencana Pelaksanaan Pembelajaran (RPP) dan hasil observasi kelas. Analisis data kuantitatif menggunakan statistik deskriptif, sementara analisis data kualitatif ini ada tiga kegiatan pokok,yaitu reduksi data, penyajian data dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa: pertama, berdasarkan analisis hasil penelitian pada tingkat reaksi, tingkat learning, dan tingkat aplikasi menyatakan bahwa kegiatan pendampingan implementasi kurikulum 2013 efektif dalam meningkatkan kemampuan guru melaksanakan pembelajaran. Kedua, terjadi peningkatan sebesar 4,8% hasil telaah RPP dan 12,77% hasil observasi pembelajaran setelah guru mengikuti kegiatan pendampingan. Ketiga, kelemahan kegiatan pendampingan implementasi kurikulum 2013 disebabkan faktor pelaksanaan yang tidak sepenuhnya mengikuti petunjuk teknis, kemampuan guru pendamping dan proses perekrutan, komitmen guru sasaran, waktu pendampingan yang terlalu singkat, dan sarana pra sarana yang dianggap kurang memadai.Kekuatan kegiatan pendampingan, antara lain: dinilai baik, membantu guru, bermanfaat dan perlu diteruskan. Selain itu kegiatan ini dirasakan dapat meningkatkan pengetahuan, pemahaman, wawasan dan pengalaman bagi guru. Berdasarkan hasil penelitian dapat disimpulkan bahwa kegiatan pendampingan implementasi kurikulum 2013 efektif dalam meningkatkan kemampuan guru melaksanakan pembelajaran.